2019
DOI: 10.1029/2018gl080620
|View full text |Cite
|
Sign up to set email alerts
|

Surface Expression of Basal and Englacial Features, Properties, and Processes of the Greenland Ice Sheet

Abstract: Radar‐sounding surveys measuring ice thickness in Greenland have enabled an increasingly “complete” knowledge of basal topography and glaciological processes. Where such observations are spatially limited, bed elevation has been interpolated through mass conservation or kriging. Ordinary kriging fails to resolve anisotropy in bed geometry, however, leaving complex topography misrepresented in elevation models of the ice sheet bed. Here, we demonstrate the potential of new high‐resolution (≤5 m) surface topogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 58 publications
2
20
0
Order By: Relevance
“…The value of outlining the onset of surface undulations for GBaTSv1 was predicated on the dominant role of the latter mechanism only. Finally, Cooper et al (2019b) found evidence of the surface expression of englacial features (e.g., disrupted deep ice) and along-flow subglacial channels in northwestern Greenland. These expressions are clearly not surface undulations that might be diagnostic of a thawed basal thermal state yet can be easily confused for them.…”
Section: Discontinued Methodsmentioning
confidence: 90%
See 2 more Smart Citations
“…The value of outlining the onset of surface undulations for GBaTSv1 was predicated on the dominant role of the latter mechanism only. Finally, Cooper et al (2019b) found evidence of the surface expression of englacial features (e.g., disrupted deep ice) and along-flow subglacial channels in northwestern Greenland. These expressions are clearly not surface undulations that might be diagnostic of a thawed basal thermal state yet can be easily confused for them.…”
Section: Discontinued Methodsmentioning
confidence: 90%
“…As part of GBaTSv1, M16 mapped the onset of surface undulations across the GrIS from surface imagery, as they are suggestive -but not definitively indicative -of the onset of substantial basal motion and hence a thawed bed. Since M16, multiple additional studies have further explored both the nature of basal roughness beneath the GrIS (Cooper et al, 2019a), how that roughness is transmitted to the surface via basal motion (Ng et al, 2018;Ignéczi et al, 2018), and made independent observations of surface texture (e.g., Cooper et al, 2019b). When considered together with de Rydt et al (2013), which formed part of the rationale for including this method in M16, we conclude that the onset of surface undulations can no longer be considered a reliable indicator of a thawed bed and we discontinue its use for GBaTSv2.…”
Section: Discontinued Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Taylor and others, 2004; Li and others, 2010; Spagnolo and others, 2017) or using standard deviation (SD; e.g. Rippin and others, 2014; Cooper and others, 2019). These methods provide a statistical analysis of the vertical variation of elevation along a transect (Cooper and others, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Processes occurring at and near the base of an ice sheet can have dramatic effects on the dynamics of the ice sheet as a whole. Subglacial hydrology, for instance, directly influences basal motion (Bartholomaus and others, 2008) and plays a role in glacial surface topography (Cooper and others, 2019). Alongside water storage, other basal processes like till deformation affect drag at the base, often to the extent that the modeled velocities of outlet glaciers vary markedly depending on basal parameters (Morlighem and others, 2010; Habermann and others, 2013; Gladstone and others, 2014).…”
Section: Introductionmentioning
confidence: 99%